An Assessment of Jurisdictional Immunity before Courts for Violation of Employment Rights by International Organizations in Sri Lanka - Sarveswaran, A. (University of Colombo, 2024)
International Organizations engage in promotion of civil, political, economic, social, and cultural rights of the people in the host countries, and they enjoy jurisdictional immunity before the domestic courts. The problem in the research ...
Keywords: Immunity; International Organizations; Domestic Courts